Kepemimpinan Transformasional Suatu Alternatif Pembelajaran Model Kepemimpinan Di Era Society 5.0 Bagi Taruna Akademi Angkatan Udara - An Naas Falag Maharta; Dody Sumardi (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2021)
The era of Society 5.0 which is a concept where the development of the Internetof Things, Big data, and Artificial Intelligence is oriented to a better human life, in contrastto the concept in the Industrial Revolution 4.0 where the technology developed is orientedtowards the productivity of business processes, this has changed the order of life. .Transformational leadership as an alternative leadership style that can adapt to the futurewith the development of the era of society 5.0 and face the critical millennial generation whoare trained to cadets at the Indonesian Air Force Academy. The writing of this manuscriptuses a descriptive analysis method that examines the literature with the opinions of expertsand several previous studies. Based on research by Megawati et al, transformationalleadership has a positive and significant effect on job performance as evidenced by the results of simple regression calculations or the results of the t-test, the t-count value is 9.451 while the t-table value is 2.024. This means that the value of t count > t table and obtains thehighest significance value of 0.00.